Role of Microalgae as a Source for Biofuel Production in the Future: A Short Review - Mustafa Jawad Nuhma; Hajar Alias; Ali A. Jazie; Muhammad Tahir (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
The continued burning of fossil fuels since the beginning of the last century led to higher emissions of greenhouse gases and thus leads to global warming. Microalgae are one of the most important sources of green hydrocarbons because this type of algae has a high percentage of lipids and has rapid growth, consumes the carbon dioxide in large quantities. Besides, the cultivation of these types of algae does not require arable land. This review aims to explain the suitability of microalgae as a biofuel source depending on the fat content, morphology, and other parameters and their effect on the conversion processes of microalgae oil into biofuels by different zeolite catalytic reactions. It also discusses in detail the major chemical processes that convert microalgae oil to chemical products. This review sheds light on one of the most important groups of microalgae (Chlorella vulgaris microalgae). This review includes a historical overview and a comprehensive description of the structure needed to develop this type of algae. The most important methods of production, their advantages and disadvantages are also deliberated in this work. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).